Evaluation of Dissolution Behavior of Paracetamol Suspensions (Dhaka University Journal of Pharmaceutical Sciences, 2008)
Ten brands of commercial paracetamol suspensions were investigated for their dissolution characteristics in 0.1 N HCl at a speed of 25 rpm using USP dissolution test apparatus II (Paddle method). It was observed that differences exist among the rate of paracetamol dissolution from the samples, particularly at the early stages. For nine of the brands, paracetamol dissolution varied between 72% and 100% at 15 minutes. One of the samples showed a very unsatisfactory rate and extent of drug dissolution as only 39% and 52% paracetamol was released after 15 and 30 minutes respectively. The effect of two commonly used suspending agents, CMC-Na and Avicel, on the release of paracetamol was studied using four laboratory-made suspensions. Retarded drug dissolution was observed which was related to the concentration of the suspending agents. Drug release kinetics followed first order as well Higuchi models. Viscosity of the samples and initial drug release was found to be inversely correlated (R2=0.9081 at 3 minutes) which faded away with the lapse of time. Key words: Paracetamol suspension, in vitro dissolution, suspending agents Â Â DOI = 10.3329/dujps.v7i1.1218 Dhaka Univ. J. Pharm. Sci. 7(1): 53-58, 2008 (June)